GABAergic role in the disruption of wild cleaner fish behaviour under high CO2. (January 2023) - Paula, José Ricardo; Cascalheira, Ligia; Oliveira, Raul; Otjacques, Eve; Frazão-Santos, Catarina; Beldade, Ricardo; Mills, Suzanne C.; Rosa, Rui
Abstract : Ocean acidification is considered to affect fish behaviour through the disruption of GABAergic neurotransmission in controlled laboratory conditions, but less is known of the GABAergic role on fish behavioural performance in the wild. Most coral reef fishes engage in complex cleaning interactions, where they benefit from ectoparasite removal and stress relief. Here, we tested whether potential ocean acidification impairment of wild cleaning interactions, between the cleaner fish Labroides dimidiatus and its clients, can be explained by the GABAA R model. We used, the GABAA receptor agonist (muscimol) and antagonist (gabazine) for the first time in the wild and tested their effects on cleaning behaviour in Moorea Island (French Polynesia) to address natural interactions and recovery capacity. After exposure to expected ocean acidification conditions, the proportion of time spent advertising cleaning services, a measure of motivation to interact, dropped significantly relative to controls. Furthermore, the GABAergic antagonist gabazine recovered most CO2 -induced behavioural alterations to control levels, consistent with the GABAA R model of altered Cl − flux in ocean acidification-exposed fish. However, muscimol treatment only produced the same behavioural alterations found with CO2 exposure in time spent advertising cleaning. Our results support the evidence that ocean acidification alters some components of cleaning behaviour through GABAA receptor modulation with potential cascading effects on coral reef health and structure. Highlights: First study on ocean acidification effects on cleaning behaviour in the wild. Ocean acidification alters some components of natural cleaning behaviour. GABAA receptor modulation is a mechanism responsible for these alterations.